Surveying Users' Perception of Academic Library Services Quality: A Case Study in Universiti Malaysia Pahang (UMP) Library - Suziyana, Mat Dahan; Mohd Yusof, Taib; Nurhaizan, Mohd Zainudin; Fadzida, Ismail (Elsevier Ltd, 2016)
Global competition among academic institutions has compelled university libraries to transform their conventional services and traditional roles to a more sophisticated, all-round service provider that can deliver their best services to their users. University libraries must cater the expansion of information sources, the high demand of users and information application as well as high student enrolments and competition among service sectors. The ability of an academic library to fulfill its user expectations will yield user satisfaction for its services. Primarily, research on assessing users' perception on the level of service quality focuses on finding ways to meet or exceed users' expectations. This study nevertheless aimed to measure students' perception and their satisfaction level of services provided by the UMP library and customized a new measuring tool on service quality and perspectives of library users based on the LibQUAL Model. A customized survey instrument was developed based on the model, consisting of 30 items measuring the level of four service dimensions and user satisfaction with an additional five items examining user satisfaction on general services. The Cronbach's alpha range is from 0.813 to 0.942, which was adequately greater than the recommended value of 0.7, thus exhibiting good internal reliability of the constructs. The result of the study reported positive values for both gap analyses in all service quality dimensions. Based on 382 respondent feedbacks, results showed that the perceived service quality level exceeded users' acceptable level on minimum service and desired service. Specifically, the users are satisfied with the services provided. Results from this study serveas a guide for effective decision making by the library in its administration and resource allocation to ensure accomplishment of the library's vision and mission.